Credit standards and capital allocation in a low interest rate environment - Svend Greniman Andersen; Andreas Kuchler (Danmarks Nationalbank, 2016)
Using firm-level data from surveys and financial statements, this paper presents an analysis of credit standards, capital allocation and financial conditions of non-financial enterprises in Denmark since the beginning of the financial crisis. The analysis indicates that low interest rates and increased competition among financial intermediaries have not lead to significant easing of credit standards for the least creditworthy firms. The current credit standards to a large extent still contribute to allocating loan capital to the most solvent and productive firms. Furthermore, the analysis indicates that Danish firms' credit demand is relatively limited, and that they have relatively good access to finance in comparison with firms in other countries. – – I dette arbejdspapir præsenteres en analyse af de senere års udvikling i kreditgivningen til danske virksomheder baseret på regnskabsdata og data fra spørgeskemaundersøgelser på virksomhedsniveau. Analysen indikerer, at det lave renteniveau og den øgede konkurrence blandt kreditinstitutterne ikke har ført til betydelige lempelser i de mindre kreditværdige virksomheders lånevilkår. Institutternes kreditvurdering giver stadig i stor udstrækning anledning til, at lånekapitalen går til de mest solide og produktive virksomheder. Endvidere indikerer analysen, at danske virksomheders låneefterspørgsel er forholdsvis afdæmpet, og at de har relativt god adgang til finansiering i sammenligning med virksomheder i andre lande.
Keywords: E44; E51; G21; G30; O16; 330; Credit Standards; Capital Allocation; Financial Frictions; Survey Data; Bank-Firm Relationships; Loan Rejection Rates; Sample Selection